WEBINAR PENGGUNAAN JAMINAN KESEHATAN NASIONAL (JKN) DI MASA PANDEMI COVID 19: WEBINAR USE OF NATIONAL HEALTH INSURANCE (JKN) DURING THE COVID-19 PANDEMIC - Gusti Agung Sri Guntari; Ni Putu Eka Febianingsih; Putu Ratna Suprima Dewi (Jurnal Suara Pengabdian 45, 2022)
The National Health Insurance (JKN) Program is part of the National Social Security System (SJSN) which is organized using the principle of mandatory social health insurance based on Undang-Undang Republik Indonesia Nomor 40 Tahun 2004. The implementation of the National Social Security System aims to provide guarantees for the fulfillment of the basic needs of a decent life for each participant and their family. In the use of JKN services, participants are required to follow the referral service procedures as stated in the regulations. During the Covid-19 pandemic, various service channels have been launched which are expected to make it easier for participants when they want to take advantage of the JKN program. So it is felt necessary to socialize to the community to understand the benefits and procedures of JKN services so that this program can be utilized as well as possible. This community service activity is carried out by providing education to private workers in Gianyar Regency. Education is carried out in the form of online webinars by utilizing zoom meeting media. After socialization, the results were obtained that there was an increase in participants' knowledge of JKN.